Anatomical Structure of Sweet Cherry Rootstocks and their Influence on Growth and Development of Cultivars: A Review - Abdikayumov, Zaynilabiddin (American Journal of Biology and Natural Sciences, 2025)
This review summarizes current knowledge on the anatomical features of sweet cherry rootstocks, identifies key structural parameters, examines the mechanisms through which rootstocks affect tree growth and productivity, and outlines research perspectives and practical implications.